1999
DOI: 10.1152/jappl.1999.87.3.1148
|View full text |Cite
|
Sign up to set email alerts
|

Patients with obstructive sleep apnea have an abnormal peripheral vascular response to hypoxia

Abstract: Patients with obstructive sleep apnea (OSA) have been reported to have an augmented pressor response to hypoxic rebreathing. To assess the contribution of the peripheral vasculature to this hemodynamic response, we measured heart rate, mean arterial pressure (MAP), and forearm blood flow by venous occlusion plethysmography in 13 patients with OSA and in 6 nonapneic control subjects at arterial oxygen saturations (Sa(O(2))) of 90, 85, and 80% during progressive isocapnic hypoxia. Measurements were also performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 14 publications
2
28
1
3
Order By: Relevance
“…However others studies have reported enhanced AI in OSAS patients in the absence of increased peripheral pressure either shortly after awakening 20 or during the episode of apnoeas. 32 Increased sympathetic activity induced by hypoxia leads to paradoxical peripheral vasoconstriction, as previously shown by Resmurg et al 33 in OSAS patients exposed to isocapnic hypoxia. This may provoke increased amplitude of pressure waves from the level of the arterioles.…”
Section: Discussionmentioning
confidence: 78%
“…However others studies have reported enhanced AI in OSAS patients in the absence of increased peripheral pressure either shortly after awakening 20 or during the episode of apnoeas. 32 Increased sympathetic activity induced by hypoxia leads to paradoxical peripheral vasoconstriction, as previously shown by Resmurg et al 33 in OSAS patients exposed to isocapnic hypoxia. This may provoke increased amplitude of pressure waves from the level of the arterioles.…”
Section: Discussionmentioning
confidence: 78%
“…Multiple pathways may therefore be implicated in potential abnormalities in efferent vasomotor control in response to hypoxia, and it is possible that several of these may be abnormal in type 2 diabetes. This is supported by findings that patients with obstructive sleep apnea and the metabolic syndrome, common comorbidities in type 2 diabetic subjects, exhibit abnormal sympathetic and paracrine control of vascular function (11,12), including abnormal vasomotor responses to hypoxia (11). To our knowledge, however, diabetic vascular responses to hypoxia have not previously been studied in humans, despite the fact that hypoxia is an important physiological stimulus associated with acute local and reflex vascular adaptations.…”
mentioning
confidence: 80%
“…Increased sympathetic nervous system activity induced by the intermittent hypoxia that characteristically accompanies OSAS appears to mediate hypertension during OSAS via a mechanism that requires changes in the vasoreactivity of resistance vascular beds such as the kidney (13)(14)(15)(16)(17)(18)(19). Indeed, sustained hypoxia (SH) does not lead to hypertension as do pharmacologically-mediated decreases of angiotensin II levels and blockade of angiotensin receptors (20,21).…”
mentioning
confidence: 99%